Analisis Strategi Pemasaran Produk Hasil Pengecoran Aluminium PT. TS Putra 2 Yogyakarta - Aura Shafa Choirunnisa; Hafizh Rizki Husain; Matrix Faqih Azizi; Muhamad Wildan Surya Prayoga; Yasmina Amalia (Jurnal Kendali Teknik dan Sains, 2024)
Industry has an important role in the economic growth of a region. The city of Yogyakarta is an example that shows the diversity of industry, especially on a small scale or home-based, such as PT. TS Putra 2 which focuses on aluminum casting. The aim of this research is to find out the right marketing strategy for PT. TS Putra 2. This research method is qualitative and quantitative based on location observations and interviews with company owners. Analysis uses the SWOT method and IFAS-EFAS method. The results of this research are the potential and opportunities to expand marketing reach and increase industrial profitability, which can be done through marketing innovation, direct sales, and utilization of marketing time. The conclusion of this research is that a marketing team is also needed to come up with marketing innovations for TS Putra 2 Cast Aluminum products.